An empirical investigation of the antecedents of salesforce control systems - Manfred Krafft (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 1997)
11 hypotheses from agency theory, transaction cost analysis, and Ouchi's theoretical approach on the impact of environmental, Company and salespeople characteristics on the design of salesforce control systems (outcome- vs. behavior-based) are summarized and tested on a data set of 270 German sales organizations. Many of the hypotheses get empirical support. Contrary to hypothesis, however, salesforce size is negatively related to the use of behavior-based control in salesforces.
Keywords: 650; Verkaufspersonal; Handelsvertretung; Vertrieb; Controlling; Prinzipal-Agent-Theorie; Transaktionskosten; Schätzung; Deutschland; Soziologie